2008
DOI: 10.1128/jvi.00561-08
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Subviral Particles of Hepatitis B Virus

Abstract: In the sera of patients infected with hepatitis B virus (HBV), in addition to infectious particles, there is an excess (typically 1,000-to 100,000-fold) of empty subviral particles (SVP) composed solely of HBV envelope proteins in the form of relatively smaller spheres and filaments of variable length. Hepatitis delta virus (HDV) assembly also uses the envelope proteins of HBV to produce an infectious particle. Rate-zonal sedimentation was used to study the particles released from liver cell lines that produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
75
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(77 citation statements)
references
References 26 publications
2
75
0
Order By: Relevance
“…This aspect is well known for patients with HBV infections, presenting with an excess (typically 1,000-to 100,000-fold) of empty subviral particles (SVPs) in addition to infectious particles. These SVPs are composed solely of HBV envelope proteins in the form of relatively smaller spheres and filaments of various lengths (47). A related mechanism is unknown for hepatitis E so far, but it is conceivable due to the results of our study.…”
Section: Discussionmentioning
confidence: 68%
“…This aspect is well known for patients with HBV infections, presenting with an excess (typically 1,000-to 100,000-fold) of empty subviral particles (SVPs) in addition to infectious particles. These SVPs are composed solely of HBV envelope proteins in the form of relatively smaller spheres and filaments of various lengths (47). A related mechanism is unknown for hepatitis E so far, but it is conceivable due to the results of our study.…”
Section: Discussionmentioning
confidence: 68%
“…For instance, HBV surface antigen (HBsAg) circulates in the blood as nucleocapsid-free, envelope-containing subviral particles that also outnumber HBV DNApositive Dane particles by 1 Â 10 3 to 1 Â 10 5 . 36 Subviral, nucleocapsid-free particles, bearing the envelope glycoprotein, are also frequently found during dengue virus or tick-borne encephalitis virus Flavivirus infections. 37,38 Subviral particles appear to exert biologically relevant properties.…”
Section: Discussionmentioning
confidence: 99%
“…The variability in source material for these experiments raises significant questions regarding the comparability of their results, as studies have demonstrated that the source of HBsAg can alter how they are bound and internalized. [33][34][35][36] Most of the studies have tried to control for 28 12 mixed patients TNF-a, IL1b, IL-6, PGE2…”
Section: Dendritic Cells In Chronic Hbv Aj Gehring and Ja D'angelomentioning
confidence: 99%